Real-World clinical outcomes of asthma patients switched from reslizumab to mepolizumab or benralizumab - Walsh, Laura J.; Casey, Deborah; Vairamani, Punitha; Arnott, Fiona; Plant, Barry J.; Murphy, Desmond M. (Frontiers in Allergy, 2023)
Introduction Approximately 3-10% of asthma patients will remain uncontrolled despite maximum, optimal conventional therapy. Treatment of severe refractory asthma often involves the use of targeted biological therapy. Randomised controlled trials have shown improvements in clinical parameters with these treatments but real-world data is lacking. Methods The clinical parameters, frequency of exacerbations, number of hospital admissions, asthma control questionnaire score (ACQ), forced expiratory volume in one second (FEV1) and maintenance oral corticosteroid (OCS) dose of twenty asthma patients switched from reslizumab to benralizumab or mepolizumab at 1 year prior and 6 months after switching were compared, with adjustments for time. Results The mean frequency of exacerbations (0.35 v 0.3) and the mean ACQ were essentially unchanged (1.6 v 1.5) following the switch. The number of hospital admissions was one in the 6 months post switch compared to one in 1-year pre switch. 25% of patients were on maintenance OCS before and after switching but one patient required an increased dose post switch resulting in an increase in the mean maintenance OCS dose (1.6mg to 2.4mg). The mean FEV1 was unchanged (80% v 77.9%) six months post switching. Regarding asthma control (n=19), 47.4% were controlled pre and post switch (ACQ<1.5), 36.8% remained uncontrolled despite switching, 10.5% improved control while 5.3% disimproved. Conclusion We present real-world clinical outcomes of asthma patients switched from reslizumab to either benralizumab or mepolizumab without a loss of clinical effectiveness in the majority.